Identification of Key Blocks Considering Finiteness of Discontinuities in Tunnel Engineering - Yang, Yong; Wang, Shuhong; Zhang, Minsi; Wu, Bo (Frontiers in Earth Science, 2022)
The traditional cutting algorithm has a clear concept and is easy to implement, but it cannot consider the finiteness of the discontinuities. Based on the traditional cutting algorithm, an accurate identification method of blocks is proposed, which can identify blocks formed by finite discontinuities and excavation surface. A visual program for identifying blocks and stability analysis is developed by using Microsoft Foundation Class and OpenGL, and then it is applied to tunnel engineering. The shape and the number of the key blocks identified by this method are not limited and consistent with actual engineering. In the case that the size of the discontinuities cannot be accurately obtained, the influence of the size change of the dominant discontinuities on the key block is discussed, which will make up the lack of parameters. The number and volume of the key blocks are large when discontinuities are assumed to be infinite, and the calculation results are conservative. However, the volume and location of the blocks have great reference value and guiding significance for practical engineering.